Comparative study of the specific activity of soft application drugs with vinpocetine - V. V. Hladyshev; D. M. Romanina; O. B. Kharaponova; A. V. Kurinnyi; I. V. Hnitko; I. O. Pukhalska; S. A. Hladysheva (Zaporozhye State Medical University, 2022)
In modern neurology, the main component of successful treatment of cerebrovascular pathology is pharmacotherapy. At the same time, the arsenal of effective medicines of evidence-based medicine in this area is quite limited. Vinpocetine (Cavinton) is one of the drugs that effectively selectively corrects cerebral perfusion. The use of alternative ways of absorption of vinpocetine (rectal and nasal) in certain soft application dosage forms will allow to significantly increase the bioavailability of the medicinal substance, reduce the level of adverse reactions from its use and expand the pharmacotherapeutic arsenal of domestic effective neuroprotective drugs. Taking into account the above, the employees of the Department of Medicines Technology of Zaporizhzhia State Medical University, on the basis of complex physical-chemical, pharmacotechnological, rheological and biopharmaceutical research, proposed rational formulations and technologies of two new soft application dosage forms of vinpocetine - rectal suppositories on a lipophilic basis and nasal cream on an emulsion basis for the therapy of arterial hypertension of II-III stages with cerebrovascular complications, reduction of the manifestation of neurological and/or mental symptoms in various forms of cerebral blood circulation insufficiency, consequences of a stroke, transient ischemic attack, etc. The aim of the work is to study the specific activity of the proposed innovative application dosage forms of vinpocetine. Materials and methods. Nasal ointment containing 0.5 % vinpocetine on an emulsion basis and rectal suppositories with vinpocetine 0.01 g on a lipophilic carrier were used as the object of preclinical studies, which ensure optimal release of the active pharmaceutical ingredient. The study of the specific activity of the developed medicinal forms of vinpocetine was carried out on a model of acute cerebrovascular accident of the type of ischemic stroke. Vinpocetin tablets (Astrapharm, Ukraine), which are used in neurological practice quite effectively and over a long period of time, were used as a comparison drug. Results. The comparative results showed that the appointment of all studied drugs led to an increase in motor activity. In addition, the administration of medicinal forms of vinpocetine reduced the development of cognitive and cognitive disorders after acute disorders of cerebral blood circulation. It was found that the highest result was shown by the group of animals that received a course of vinpocetine intranasally. In the groups of animals that received vinpocetine for 4 days, markers of oxidative stress - aldehyde phenylhydrazones and ketone phenylhydrazones - were significantly reduced. The highest activity was demonstrated by the pharmaceutical form of vinpocetin, which was used intranasally for 4 days. The introduction of dosage forms of vinpocetine exerted an energizing effect, which was expressed in an increase in the level of macroergic phosphates. Evidently, vinpocetine has a direct positive effect on the three-carbon sections of the Krebs cycle and increases the production of adenosine triphosphate (ATP). At the same time, the vinpocetine nasal cream applied intranasally for 4 days demonstrated the greatest energizing activity. Conclusions. Preclinical studies of the developed application soft medicines with vinpocetine on the model of acute cerebrovascular accident type ischemic stroke experimentally confirmed the expressed neuroprotective activity of rectal suppositories and nasal cream with vinpocetine and it was found that the effectiveness of therapy with these application medicinal forms is demonstrably higher than that in comparison with oral tablet means.